Community Influence as an Explanatory Factor Why Roma Children Get Little Schooling - Oded Stark; Ruxanda Berlinschi (Institute of Labor Economics (IZA), 2020)
Parents who experience poverty and who want to provide their children with an escape route can be expected to encourage and support their progeny's education. The evidence that Roma parents behave differently is unsettling. In this paper we test empirically an explanation for that behavior. The explanation is based on a theory (Stark et al. 2018) that can be "borrowed" to rationalize the enforcement of norms of little formal education in underprivileged communities. An analysis of survey data collected in Roma communities in four Central and Eastern European countries lends support to the explanation. The analysis reveals a strong negative correlation between the influence of the Roma community on an individual member's life and the importance accorded by the individual to formal schooling for children. The correlation is robust to controlling for standard determinants of attitudes towards schooling, such as poverty, unemployment, labor market discrimination, and parents' educational attainment. The analysis suggests that policy interventions aiming to increase the formal education of Roma children need to reckon with the influence of Roma community norms on individual choices.
Keywords: J15; J24; J70; O12; Z13; 330; community influence; social norms; social distance; exposure to relative deprivation; Roma communities; formal education of children